دراسة في علوم القرآن وتفسيره: Studies in the Science of the Qur'an and Its Interpretation - Rifky, Rifky; Maksum, Muh. Nur Rochim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study discusses a brief study of the Science of the Qur'an and its Tafsir, which is one of the most noble and high-ranking sharia sciences, because it is directly related to the Kalam of Allah SWT, as well as its great influence in the correct understanding of the Qur'an and its application. The purpose of this research is to explain the concept of the Qur'anic Science, the virtues of studying it, and its development throughout the ages, focusing on its main topics, such as the collection of the Qur'an, knowing the Mecca and Madani, as well as the methods of interpretation, especially the tafsir bil-ma'tsur (based on history) and the tafsir bil-ra'yi (based on opinion). This research also discusses the concept of collecting the Qur'an both through memorization and writing, and explains the historical stages of the collection of the Qur'an during the time of the Prophet صلى ﷲ عليه وسلم, then during the time of the Caliph Rashidun, and highlights the thoroughness of the scientific methods applied by the Companions in keeping the Qur'an from deviations. In addition, this study discusses the problems of Mecca and Madani, explaining the definition, how to know both, and their benefits in understanding the context of the verses of the Qur'an, knowing nasikh and mansukh, and developments in legislation. This research also pays important attention to the method of interpretation, by explaining the position of tafsir bil ma'tsur as the main basis in understanding the Qur'an, because it is based on authentic texts from the Qur'an, hadith, and the sayings of the companions and tabiin. Then, this study discusses the interpretation of bil-ra'yi, explaining the difference between a good opinion that follows scientific rules and a reprehensible opinion based on lust and ignorance. This research ends by explaining the requirements of a mufassir and ethics in tafsir, emphasizing the importance of not talking about the Qur'an without knowledge, as well as the need for sincerity, piety, and correct methods. The conclusion of this study is that studying the science of the Qur'an is a solid foundation for the correct understanding of the text of the Qur'an, strengthens the faith, and protects the interpretation from deviations, which shows the importance of attention to this science in terms of teaching, learning, and research.